Analysis of monoterpene variation in natural stands and plustrees of Pinus sylvestris in Finland. - Muona, Outi; Hiltunen, Raimo; Morén, Erkki; Shaw, D. (Silva Fennica, 1986)
Variation of monoterpene composition of L. was studied in Southern, Central and Northern Finland using data from both natural stands and plus trees. The natural stands were analysed using different techniques and for fewer terpenes than the plus trees.Pinus sylvestris